The essential oil from the rhizomes of Stahlianthus involucratus attenuates the progression of vascular aging and atherosclerosis by regulating Nrf2-mediated mitochondrial quality - Li, Jianmei; Wang, Zaishang; Wang, Yu; Lin, Jiaxin; Tang, Ning; Zheng, Chu; Xu, Qin (Frontiers in Pharmacology, 2025)
IntroductionAtherosclerosis (AS), characterized by chronic inflammation within the vasculature, is linked to endothelial dysfunction and oxidative stress. The senescence of vascular endothelial cells (VECs) serves as a pathological basis for AS. Stahlianthus involucratus (King ex Baker) Craib ex Loes is a folk medicinal plant commonly used in Guangxi has its rhizome as the active component. In traditional Chinese medicine, it is believed to promote blood circulation, remove blood stasis, stop bleeding, and disperse accumulated blood. Essential oil extracted from Stahlianthus involucratus rhizomes (EOSIR) is a key bioactive component. However, little research has been reported on the effects of EOSIR on cardiovascular disease.MethodsValidation techniques, including H&E staining and western blotting, were employed to assess the efficacy of EOSIR in both in vivo and in vitro models of AS.ResultsIn vivo experiments, EOSIR decreased plaque volume in atherosclerotic vessels of mice. Activation of the Nrf2 signaling pathway by EOSIR alleviated ox-LDL-induced injury in HUVECs, including a reduction in cellular senescence, apoptosis, ROS, and mitochondrial membrane potential, effects that were reversed by Nrf2 silencing. EOSIR also restored mitochondrial morphology in cells and enhanced Nrf2 expression as well as ATP levels in aortic tissue. Both in vivo and in vitro, EOSIR upregulated the Nrf2, NQO1, and HO-1 expression, downregulated Keap1 expression, and improved the mitochondrial-associated protein expression.DiscussionThese findings suggest that EOSIR may prevent the onset of AS both in vivo and in vitro by modulating the mitochondrial quality control system through the Nrf2 signaling pathway.